Kecenderungan Sokongan Politik Belia: Satu Kajian di Negeri Perak Darul Ridzuan - Sahiri, Meor Ban (2010)
The purpose of this study is to determine youths political support inclinations in the state of Perak. Only three parliamentary area were chosen are P 57 Parit Buntar, P 59 Bukit Gantang and P 60 Taiping and the respondent were the Malays youth from the age of 18 to 40 years. Security, economic, communication and leadership factors are among independent variable whereas political support inclinations were the dependent variable. Correlation and regression test as well as difference test were implemented based on information derived from data gathered through questionnaire forms which circulated and as much as 461 forms was returned and screening made prior to analysis. Accumulated data were analyzed by using SPSS version 16. ANOVA test perpetrated upon demographic factors namely age, sex and education level in order to see the differences. Result from the test show that only age give different effects on variable occurred in P 60 Taiping Parliamentary area. Results from analysis test show that there is significant correlation between independents variable and the dependent variable. Result of the multiple regression test show that not all independent variable have a significant influence with dependent variable. It proven that only P 59 Bukit Gantang has the significant influences among independents variable and dependent variable. Whereas for P 57 Parit Buntar only communication and leadership factors have the significant influence while for P 60 Taiping the youths do not consider the economic factor. However the research has made the objective as well as replying the question raise in the issues of this study.